2008
DOI: 10.1111/j.1537-2995.2008.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of a transfusion policy of D+ red blood cells into D− patients

Abstract: The use of D+ RBCs in selected D- patients does not induce adverse reactions and allows the saving of a significant number of D- RBCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 16 publications
4
77
2
Order By: Relevance
“…First, the frequency of anti-D alloimmunization following D+ RBC transfusion ranged from 21 to 33% in D- patients who were not iatrogenically immunosuppressed. Second, patients who did not develop anti-D received more D+ RBC units when compared with patients who developed anti-D, although the difference was not statistically significant in one study [104], and the statistical analysis was not reported in the remaining two studies [105,106]. …”
Section: Part 2: Plt Transfusion and The D Antigenmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the frequency of anti-D alloimmunization following D+ RBC transfusion ranged from 21 to 33% in D- patients who were not iatrogenically immunosuppressed. Second, patients who did not develop anti-D received more D+ RBC units when compared with patients who developed anti-D, although the difference was not statistically significant in one study [104], and the statistical analysis was not reported in the remaining two studies [105,106]. …”
Section: Part 2: Plt Transfusion and The D Antigenmentioning
confidence: 99%
“…However, one prospective and three retrospective observational studies published in the last decade showed us two intriguing sets of data [104,105,106,107]. First, the frequency of anti-D alloimmunization following D+ RBC transfusion ranged from 21 to 33% in D- patients who were not iatrogenically immunosuppressed.…”
Section: Part 2: Plt Transfusion and The D Antigenmentioning
confidence: 99%
“…Even after transfusion of normal D-positive units, only about 21-31% of patients develop an anti-D [10,11,12]. Weak D and DEL units are likely considerable to be less immunogenic.…”
Section: A General View On Anti-d Immunizationmentioning
confidence: 99%
“…ABO-mismatched transplantation may have different effects if G-CSF-primed PBSC or CB grafts or new conditioning regimens are used [11]. Besides the ABO blood group system, Rhesus (Rh) antigens, especially the D antigen, are clinically the most significant factors for alloimmunization that usually occur after exposure of RhD-negative individuals to RhD-positive blood components [12]. Studies in HSCT recipients have shown an incidence of 10% of anti-D alloimmunization in RhD-positive patients with a RhD-negative donor [13,14].…”
Section: Introductionmentioning
confidence: 99%